The relationship between problematic internet use and psychological distress in older Chinese teachers (40+) during different stages of the COVID-19 pandemic: three cross-sectional studies - Chen, Xiu-Mei; Wang, Li-Feng; Liao, Xiao-Ling; Wang, Shuai; Yang, Lan; Chen, I-Hua (Frontiers in Public Health, 2024)
BackgroundDespite a consensus on the negative implications of problematic internet use (PIU) for mental health, there is a notable gap in research concerning older demographics, particularly older teachers. This study aimed to investigate the prevalence of PIU and its impact on the mental wellbeing of this population.MethodsThree sub-studies were conducted: Study 1 (2020) investigated how fear induced by COVID-19 influenced PIU and psychological distress among 3,929 older teachers. Study 2 (2021) examined the effects of PIU on psychological needs thwarting (the frustration of basic psychological needs) and psychological distress, involving 3,502 participants. Study 3 (2022) explored the impact of PIU on occupational burnout and psychological distress, with 1,276 participants. The Generalized Linear Model in Jamovi 2.3.23 was used to evaluate the three mediation models.ResultsThe three sub-studies revealed a high prevalence of PIU among older teachers (27.4% in Study 1, 27.4% in Study 2, and 24.5% in Study 3). High levels of PIU were associated with elevated psychological distress during the 3 years of the COVID-19 pandemic. In Study 1, fear of COVID-19 indirectly influenced psychological distress through PIU as a mediator. In Studies 2 and 3, respectively, psychological needs thwarting and occupational burnout mediated the relationship between PIU and psychological distress.ConclusionThis study confirmed the high prevalence of PIU among older school teachers and the detrimental effect of PIU on psychological needs thwarting, occupational burnout, and psychological distress. Given these findings, education authorities and school management should take proactive steps to mitigate PIU and ensure the health and wellbeing of older teachers.